The Effects of Dried Knotweed (Polygonum cognatum Meissn.) Leaves on Egg Quality, Egg Antioxidant Capacity, and Some Serum Biochemical Parameters in Laying Hens - KILINÇ, Gözde (MAS Journal of Applied Sciences, 2023)
In this study, the possibilities of using different levels of dried knotweed (Polygonum cognatum Meissn.) leaf (KMY) powder were investigated in laying hens. For this purpose, 4 groups were formed, 24 in each group, and a total of 96 hens (30 wk-old, Lohmann) were divided to 4-storey cages as individual. The control group (KMY-0) was fed with basal diet without additives. Experimental groups (KMY-1, KMY-2, and KMY-3) were fed by adding 0.5, 1, and 1.5 g/kg KMY powder to the basal diet, respectively. The trial lasted for a total of 9 weeks, one week of which was acclimatization period. Egg quality characteristics, egg yolk TBARS and DPPH levels, and some serum biochemistry parameters were evaluated. Egg shape index (P<0.05), egg yolk TBARS value (day 1, P<0.001; day 28, P<0.05), and serum total protein (P<0.05) and LDL (P<0.05) concentrations was determined to be significantly affected from KMY powder in diet. The highest egg shape index value, and serum total protein level and the lowest egg yolk TBARS and, serum LDL level were in the KMY-3 group. In the polynomial analysis, the linear effect was significant in terms of egg yolk TBARS level and serum total protein, and LDL concentration. It was determined that the serum LDL level decreased with increasing levels of KMY. As a result, it is seen that KMY powder can be used in delaying lipid oxidation and reducing LDL in diets of laying hens. It is thought that especially the 1.5 g/kg level in diets may have positive effects, but there is a need for comprehensive studies on the subject.